Reference Points and Contractual Choices: An Experimental Examination. Issue 3 (19th August 2013) - Feldman, Yuval; Schurr, Amos; Teichman, Doron
<x xml:space="preserve">Abstract</x> This article focuses on the influence of framing on the way people understand their contractual obligations. A large body of both psychological and economic studies suggests that people treat payoffs framed as gains and payoffs framed as losses distinctly. Building on these studies, we hypothesize that the ways parties understand their duties are affected by the way in which they are framed. More specifically, we expect that promisors will tend to adopt a more self‐serving interpretation when they are making decisions in the domain of losses. To test this prediction, we run a series of four experiments that are all based on a between‐subject design. The first two studies utilize experimental surveys that measure and compare participants' attitudes toward a contract interpretation dilemma. The third and fourth studies are incentive‐compatible experiments, in which participants' actual interpretive decisions determine their payoff. All four experiments confirm our basic hypothesis and show that framing contractual payoffs as losses rather than as gains raises parties' tendency to interpret their obligations selfishly. These findings refine some of the previous understanding regarding the ability of penalties to optimize parties' contractual behavior, especially in situations in which monitoring is limited. Based on these findings, the article revisits some of the basic questions of contract law, shedding new light on an array of issues such as the law of liquidated damages and the optimal design of contracts.